Etching-induced damage in heavily Mg-doped p-type GaN and its suppression by low-bias-power inductively coupled plasma-reactive ion etching. (13th January 2021) - Kumabe, Takeru; Ando, Yuto; Watanabe, Hirotaka; Deki, Manato; Tanaka, Atsushi; Nitta, Shugo; Honda, Yoshio; Amano, Hiroshi
Abstract: Inductively coupled plasma–reactive ion etching (ICP–RIE)-induced damage in heavily Mg-doped p-type GaN ([Mg] = 2 × 10 19 cm −3 ) was investigated by low-temperature photoluminescence (PL) and depth-resolved cathodoluminescence (CL) spectroscopy. From PL measurements, we found broad yellow luminescence (YL) with a maximum at around 2.2–2.3 eV, whose origin was considered to be isolated nitrogen vacancies ( V N ), only in etched samples. The depth-resolved CL spectroscopy revealed that the etching-induced YL was distributed up to the electron-beam penetration depth of around 200 nm at a high ICP–RIE bias power ( P bias ). Low-bias-power (low- P bias ) ICP–RIE suppressed the YL and its depth distribution to levels similar to those of an unetched sample, and a current–voltage characteristic comparable to that of an unetched sample was obtained for a sample etched with P bias of 2.5 W.